2018
DOI: 10.1002/sim.7992
|View full text |Cite|
|
Sign up to set email alerts
|

Minimum sample size for developing a multivariable prediction model: PART II ‐ binary and time‐to‐event outcomes

Abstract: When designing a study to develop a new prediction model with binary or time‐to‐event outcomes, researchers should ensure their sample size is adequate in terms of the number of participants (n) and outcome events (E) relative to the number of predictor parameters (p) considered for inclusion. We propose that the minimum values of n and E (and subsequently the minimum number of events per predictor parameter, EPP) should be calculated to meet the following three criteria: (i) small optimism in predictor effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
613
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 600 publications
(662 citation statements)
references
References 59 publications
6
613
0
Order By: Relevance
“…Since this is the first study to examine the relationship between load and hamstring injury in football, a formal a priori sample size estimation was not possible using existing studies as per the TRIPOD (Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis) statement 22‐item checklist . Accordingly, to inform the design of future studies, Cox‐Snell pseudo‐ R 2 ( R 2 CS ) statistics were reported as measures of model overall performance . Outcome statistics are reported as point estimates and 95% confidence intervals (CI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this is the first study to examine the relationship between load and hamstring injury in football, a formal a priori sample size estimation was not possible using existing studies as per the TRIPOD (Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis) statement 22‐item checklist . Accordingly, to inform the design of future studies, Cox‐Snell pseudo‐ R 2 ( R 2 CS ) statistics were reported as measures of model overall performance . Outcome statistics are reported as point estimates and 95% confidence intervals (CI).…”
Section: Methodsmentioning
confidence: 99%
“…Given the novelty of our study, a formal a priori sample size estimation informed by the precision of coefficient estimates or relevant model statistics from any existing study could not be performed. Nevertheless, recent advances in the procedures for determining minimum sample size now permit a robust appraisal of the sample size requirements based on pseudo‐ R 2 statistics . Therefore, we reported the recommended statistics, which can be used by researchers and clinicians to inform sample size estimation for future investigations in this field (Table ).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While no consensus currently exists on the sample sizes required for prognostic prediction, the required sample size depends on several factors, including the number of predictors, total sample size, and number or proportion of events 5859. Thus, large sample sizes could be needed to reliably develop a prognostic model, especially when tens or hundreds of candidate predictor variables are considered.…”
Section: Threats To the Viability Of Rct Data Usementioning
confidence: 99%
“…(17) However, recent studies have shown that such a rule of thumb is not adequate because the number of events is dependent on the number of risk factors/parameters, proportion of variance explained, shrinkage factor (ie, bias between sample statistics and population parameters), and incidence of disease. (18) For example, a study on fracture risk with 10 risk factors, assuming 10% fracture incidence, shrinkage factor of 0.90, and 20% expected variance explained, would require approximately 400 individuals for a multivariable logistic regression model. However, if the proportion of variance explained is 10%, the required sample size would increase to 850 individuals.…”
Section: Fundamentals Of Statistical Analysismentioning
confidence: 99%